Peran Pemerintah Daerah dalam Pelayanan Kesehatan HIV/AIDS di Kota Kupang: Kajian Kinerja Birokras - Marianus Siga; Yohana Kristina Nima; Yufitris Naitboho; Febiana Elisabet Mase; Inriwati Ora; Fadil Mas'ud (CV. ITTC INDONESIA, 2026)
HIV/AIDS in Kupang City continues to face limited access to health services, high levels of social stigma, and suboptimal bureaucratic performance in the delivery of health services. These conditions result in low utilization of health services and a decline in the quality of life for people living with HIV/AIDS (PLWHA). The main issue addressed in this study is the ineffective role of the local government and bureaucracy in improving the quality of HIV/AIDS health services in Kupang City. This study aims to analyze the role of the local government and the influence of bureaucratic performance in improving the quality of HIV/AIDS healthcare services. The research method used is a literature review employing a qualitative descriptive approach through the examination of various relevant journals, books, and scientific documents. The analytical techniques used in this study are content analysis and comparative analysis to compare various findings from previous studies related to HIV/AIDS health services. The results of the study indicate that the local government plays a strategic role through policy formulation, the provision of health facilities, and the implementation of community-based public education programs. However, challenges remain in policy implementation, the distribution of health services, and social acceptance of PLHIV. An effective, transparent, and innovative bureaucracy has proven capable of improving the quality of services, accessibility, and public trust in HIV/AIDS health services. The integration of technology and bureaucratic reform are key factors in achieving responsive, inclusive, and sustainable HIV/AIDS health services.